Elaine and John Steinbeck at Elaine's birthday party. (Sag Harbor, New York; USA, 2022)
Elaine and John Steinbeck at Elaine's birthday party. Elaine, seated, voices surprise at the poster gift being presented. See photo 3-133. John stands holding a large package and taking a drink. Original in safe.